Medicinal plants used for the management of respiratory diseases in Zimbabwe: Review and perspectives potential management of COVID-19 - Nyagumbo, Elliot; Pote, William; Shopo, Bridgett; Nyirenda, Trust; Chagonda, Ignatius; Mapaya, Ruvimbo J; Maunganidze, Fabian; Mavengere, William N; Mawere, Cephas; Mutasa, Ian; Kademeteme, Emmanuel; Maroyi, Alfred; et al. (Elsevier, 2022)
Respiratory diseases have in the recent past become a health concern globally. More than 523 million cases of coronavirus disease (COVID19), a recent respiratory diseases have been reported, leaving more than 6 million deaths worldwide since the start of the pandemic. In Zimbabwe, respiratory infections have largely been managed using traditional (herbal) medicines, due to their low cost and ease of accessibility. This review highlights the plants' toxicological and pharmacological evaluation studies explored. It seeks to document plants that have been traditionally used in Zimbabwe to treat respiratory ailments within and beyond the past four decades. Extensive literature review based on published papers and abstracts retrieved from the online bibliographic databases, books, book chapters, scientific reports and theses available at Universities in Zimbabwe, were used in this study. From the study, there were at least 58 plant families comprising 160 medicinal plants widely distributed throughout the country. The Fabaceae family had the highest number of medicinal plant species, with a total of 21 species. A total of 12 respiratory ailments were reportedly treatable using the identified plants. From a total of 160 plants, colds were reportedly treatable with 56, pneumonia 53, coughs 34, chest pain and related conditions 29, asthma 25, tuberculosis and spots in lungs 22, unspecified respiratory conditions 20, influenza 13, bronchial problems 12, dyspnoea 7, sore throat and infections 5 and sinus clearing 1 plant. The study identified potential medicinal plants that can be utilised in future to manage respiratory infections.